STUDI MINAT PEMBELI ONLINE SHOP DENGAN KUALITAS PELAYANAN DAN KEPUASAN KONSUMEN SEBAGAI PREDIKTOR DI DESA BERGAS KIDUL KECAMATAN BERGAS KABUPATEN SEMARANG - Erna Nur Wahidah,; Aletta Dewi Maria Th,; Tri Maryani,; Idah Kusuma Dewi, (Journal of Innovation Research and Knowledge, 2025)
This study was conducted in Bergas Kidul Village, Bergas District, Semarang Regency. The aim of this study is to find out how service quality and customer satisfaction impact buyers' interest in online shops in Bergas Kidul Village partially and how buyer satisfaction and service quality impact online buyers' interest in Bergas Kidul Village together. To calculate and produce 95 people living in Bergas Kidul Village, Bergas District, Semarang Regency as samples, the Slovin formula was used. The research results show that customer satisfaction and service quality have an impact on buyer interest in online shops in Bergas Kidul Village partially, and both have an impact on buyer interest in online shops in Bergas Kidul Village together